Do internet and mobile usage affect the Democracy-economic growth nexus in Africa? - Toyo Amegnonna Marcel Dossou; Kihumuro Jotham; Kouessi P. Dossou; Emmanuelle Ndomandji Kambaye; Simplice Asongu; Alastaire Sèna Alinsato (African Governance and Development Institute (AGDI), 2023)
Recently, many studies have examined the ICT-economic growth relationship and the democracy-economic growth linkage with conflicting results. However, the study on the moderating effect of internet and mobile usage on the democracy-economic growth relationship is very scanty. This study, therefore, contributes to the economic development literature by examining the impact of internet and mobile usage on the democracy-economic growth relationship in 26African economies over the period 2000-2020. The panel corrected standard errors (PCSE) estimation technique has been applied. The results show that improving democratic system in Africa can foster economic growth. Moreover, the result reveals that increasing internet and mobile usage can boom economic growth in Africa. Furthermore, the results reveal that the interaction between internet and mobile usage and democracy can boost economic growth in Africa. Policy implications regarding the moderating effect of internet and mobile usage on the democracy-economic growth nexus are discussed.
Keywords: 330; Democracy; internet and mobile usage; Economic growth; Africa